2017
DOI: 10.1016/j.crm.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the evolution of the 2014–2016 summer rainfall seasons in southern Africa: Key lessons

Abstract: a b s t r a c tThe recent 2015/16 summer rainfall season in the terrestrial Southern African Development Community (SADC) region appears to be the most severe since the droughts of the early 1980s and 1990s; with well-publicized significant impacts on agriculture and food security. Impacts have been particularly concerning since the 2015/6 season followed a poor rainy season in 2014/15, in certain areas compounding already compromised production (total maize production was, for example, down 40% relative to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 11 publications
4
66
0
Order By: Relevance
“…The drought began to unfold in 2015 when there was significantly lower than average rainfall feeding into Cape Town's water supply system (Knight, ; Otto, Wolski, Lehner, Tebaldi, et al, ; Wolski, ). The Western Cape province was not unique in experiencing unusual hydrological conditions, as Southern Africa as a whole has been experiencing longer‐term drying trends (Archer et al, ). However, as the drought worsened in 2016, the City of Cape Town's water managers remained confident in the system's ability to withstand it (in‐person interviews with city officials in 2016, see also Knight, ).…”
Section: Uncertainty Unpredictability Variabilitymentioning
confidence: 99%
“…The drought began to unfold in 2015 when there was significantly lower than average rainfall feeding into Cape Town's water supply system (Knight, ; Otto, Wolski, Lehner, Tebaldi, et al, ; Wolski, ). The Western Cape province was not unique in experiencing unusual hydrological conditions, as Southern Africa as a whole has been experiencing longer‐term drying trends (Archer et al, ). However, as the drought worsened in 2016, the City of Cape Town's water managers remained confident in the system's ability to withstand it (in‐person interviews with city officials in 2016, see also Knight, ).…”
Section: Uncertainty Unpredictability Variabilitymentioning
confidence: 99%
“…The 2015/16 season had very low lake water levels [67] and was characterized by low rainfall due to an El Niño-induced drought that affected Southern Africa [68]. Low water levels amplify sensitivity as fishers reported that their fishing grounds were reduced as a result.…”
Section: Threats Affecting Fishers and Conflicts With Other Lake Usersmentioning
confidence: 99%
“…The region exhibits relatively low adaptive capacity (Kusangaya et al 2014), as the El Niño drought event of 2015/16 amply demonstrates (Archer et al 2017;Baudoin et al 2017). Therefore, future changes in rainfall over this region need to be identified and understood, such that stakeholders, from civil society to policymakers, can make informed decisions about future adaptation planning in key sectors (Collins et al 2012;Knutti et al 2010).…”
Section: Introductionmentioning
confidence: 99%